“That Felt Real to Me”: When Reality Theatre and Reality Television Collide - Mcleod, Kimberley (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (Graduate Centre for the Study of Drama, University of Toronto, 2018)
In an episode of his satirical television show Nathan for You, comedian Nathan Fielder creates an original theatre production in order to exploit a legal loophole that allows smoking in bars if it is part of a performance. The project begins as a one-off invisible theatre performance but quickly morphs into an experiment in the possibilities and limits of theatre of the real when Fielder re-stages the initial event with actors so the production can be repeatable, and thus marketable as a consistent product. In the “Smokers Allowed” episode, Fielder’s comedic attempts to painstakingly recreate events highlight the inherent ridiculousness of reality-based performances. This Nathan for You episode brings together two related approaches to performance—reality television and reality theatre—that are linked through their focus on reality, but which tend to diverge in content and reception. In doing so, he reveals a double standard in the cultural valuation of reality television and theatre of the real—one that ironically relies on an anti-theatrical bias towards televisual forms. At a time when there is heightened anxiety about what constitutes reality and an increasing concern that all realities are constructed, Fielder’s satire raises a number of pressing questions related to performance and the real, including: How might a satirical, comedic approach to theatre of the real help us understand omissions and biases within this form? How might acknowledging that all reality-based art forms are fundamentally absurd open up this field to new possibilities?